Peran Komunikasi Guru SDIT Al-Uswah dalam Meningkatkan Motivasi Belajar Siswa - Vajrani, Nadinda Zulfa (Prisani Cendekia Institute, 2024)
The focus of this research is the role of teacher communication in increasing the motivation of grade I students of SDIT Al-Uswah. The purpose of this study is to describe the role of teacher communication in increasing the learning motivation of SDIT Al-Uswah students. The research method used in this research is qualitative method. Data collection techniques using observation, interview and documentation techniques. The result of this research is an understanding of the diverse teaching strategies and methods applied by teachers at SDIT Al-Uswah. This variety can affect students' level of acceptance of teaching which will ultimately contribute to increasing students' learning motivation in the classroom. This is because Islamic schools will generally have a different system from public schools, including in communication between teachers and students. Teachers are expected to provide lessons on the values of courtesy, gentleness in interacting with teachers and friends, fostering mutual affection, cultivating mutual respect and encouraging a spirit of help among fellow students.